Perceiving the Impact of Visual Media: A Phenomenological Study on Teacher Experiences in Teaching English to Elementary School - Hafsa, Sri Sholeha; Wahidah, Wahidah; Idami, Zahratul (the Study Program of Education for Islamic Elementary School Teachers (Undergraduate), 2024)
Teaching English to children is crucial. English plays a significant role internationally, providing access to information and technology. Effective teaching for young learners requires good planning, suitable methods, and appropriate materials. The purposes of this study were to (1) identify the visual aids that English teachers at MIN 2 Langsa utilize to teach English to primary pupils, and (2) investigate the teacher's experiences with these aids. Data collection was done in December 2023 through a fifth-grade English teacher at MIN 2 Langsa. The phenomenological approach was combined with a qualitative method in this study. An interview and an observation served as the instruments. The purpose of the observation was to see how the fifth-grade pupils at MIN 2 Langsa's teachers using media, and the interview was given to the English teacher to learn more about the teacher's expertise with visual media. The results of this study demonstrated that the types of media that teachers used to teach English included whiteboards, English textbooks, dictionaries, posters, pictures, games, and other objects that were nearby. The interview with the teacher revealed that, depending on the subject, she employed visual aids to simplify the English lesson and help the pupils understand it better.